KONSEP DAN GAGASAN PELAKSANAAN PENDIDIKAN ANTI KORUPSI BAGI ANAK PENCIPTA GENERASI BEBAS KORUPSI - Albert Andre Saturnus (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
In Indonesia, corruption is a national crime. Just think about the damage that could be done to Indonesia in the future if corruption there is allowed to fester until it becomes uncontrollable. If we care about the country's future, we must invest in our children's education, and that includes teaching them to resist the temptation to engage in corrupt behavior. The anti-corruption curriculum teaches young people that corruption is harmful to everyone and that it spreads like a virus through a society. Please elaborate on the idea of anti-corruption education as it is presented in the classroom. It is imperative that this educational idea come from the various institutions that work with children, including the administration. The idea proposed by the author is to hold anti-corruption training for children from the beginning of education to the end of their education, besides that the government intends to provide anti-corruption training and support services to teachers.